Proposed upgrading to the existing interior design of children section in Penang State Public Library at JKR 2118 Jalan Perpustakaan, Seberang Jaya, 13700 Prai, Pulau Pinang for Penang Public Library Corporation / Nurhidayou Rosli - Rosli, Nurhidayou (Faculty of Architecture, Planning and Surveying, 2012)
The project for final project is upgrade the Penang Public State Library.at JKR 2118 Jalan Perpustakaan, Seberang Jaya 13700 Prai Pulau Pinang. This project is to increase a reading culture among people of age in Penang and give a new environment and design in library so that people would like to came. The research aim for upgrading of PPAPP is to learn about the system and space that needed in the library. In addition, the research objective in this project is to identify the design problem at existing site before proposed upgrading the project. There are three phase of methodology procedure in providing this project will finish successfully. The first process (project proposal)are inculding conducting feasibility study on existing site and gathering data from client for design requirement. The second phases (research field) is started with two case study on the similar type of library in local study and two from precedent study, its mean an oversea public library. In addition, perform on site analysis and building analysis of PPAPP. The final phases is design proposal. In this phase is to construct and design the project based on space requirement in site. Case study on local location at Perpustakaan Perbadanan Awam Selangor at Seksyen 13, 40100 Shah Alam and UTP Library at Sri Iskandar, Perak while case study on oversea is The Seattle Public Library and The Mcallen Public Library. The objective design of this project is to give a library more efficiently and attractive library for people to experience the enjoyment of reading and the excitement of discovering knowledge and works of the imagination. The design problem in the library from the observation on site is based on finishes such as floor, space planning and furniture arrangement, lighting that used and the safety items not located in the right palce. In addition, the design problem solution is solve the problem that identify to better than before based on good design and planning.